Impact of novel coronavirus Disease-19 (COVID-19) pandemic in Italian pediatric emergency departments: a national survey - Valentina Talarico; Luciano Pinto; Gian Luigi Marseglia; Antonella Centonze; Concetta Cristofaro; Rocco Reina; Agostino Nocerino; Riccardo Lubrano; Stefania Zampogna; SIMEUP research group (BMC, 2021)
Abstract Background Coronavirus Disease-19 (COVID-19) has rapidly become a pandemic emergency, distressing health systems in each affected country. Preparation strategies for managing this pandemic have been keys to face the COVID-19 surge all over the world and all levels of care. Materials and Methods During the epidemic, the Italian society of pediatric emergency-urgency (SIMEUP) promoted a national survey aiming to evaluate preparedness and response of pediatric emergency departments (PED) critical in ensuring optimal management of COVID-19 cases. Results Our results suggest that Italian PED have promptly set a proactive approach to the present emergency. 98.9% of the hospitals have defined special pathways and assistive protocols concerning the management of pediatric COVID-19 cases. The highest percentage of application of the measures for preventive and protective for COVID-19 concerned the use of personal protective equipments. Conclusions Results show that the following measures for pediatric patients, admitted in PED, have been promptly implemented throughout the whole country: eg. use of protective devices, pre-triage of patients accessing the hospital. Despite COVID-19 being a new threat, we have shown that by developing an easy-to-follow decision algorithm and clear plans for the interventional platform teams, we can ensure optimal health care workers and patients' safety.